Current real-life use of vasopressors and inotropes in cardiogenic shock - adrenaline use is associated with excess organ injury and mortality - Tarvasmäki, Tuukka; Lassus, Johan; Varpula, Marjut; Sionis, Alessandro; Sund, Reijo; Køber, Lars; Spinar, Jindrich; Parissis, John; Banaszewski, Marek; Silva Cardoso, Jose; Carubelli, Valentina; Di Somma, Salvatore; et al. (Critical care (London, England), 2016)
BACKGROUND: Vasopressors and inotropes remain a cornerstone in stabilization of the severely impaired hemodynamics and cardiac output in cardiogenic shock (CS). The aim of this study was to analyze current real-life use of these medications, and their impact on outcome and on changes in cardiac and renal biomarkers over time in CS. METHODS: The multinational CardShock study prospectively enrolled 219 patients with CS. The use of vasopressors and inotropes was analyzed in relation to the primary outcome, i.e., 90-day mortality, with propensity score methods in 216 patients with follow-up data available. Changes in cardiac and renal biomarkers over time until 96 hours from baseline were analyzed with linear mixed modeling. RESULTS: Patients were 67 (SD 12) years old, 26 % were women, and 28 % had been resuscitated from cardiac arrest prior to inclusion. On average, systolic blood pressure was 78 (14) and mean arterial pressure 57 (11) mmHg at detection of shock. 90-day mortality was 41 %. Vasopressors and/or inotropes were administered to 94 % of patients and initiated principally within the first 24 hours. Noradrenaline and adrenaline were given to 75 % and 21 % of patients, and 30 % received several vasopressors. In multivariable logistic regression, only adrenaline (21 %) was independently associated with increased 90-day mortality (OR 5.2, 95 % CI 1.88, 14.7, p = 0.002). The result was independent of prior cardiac arrest (39 % of patients treated with adrenaline), and the association remained in propensity-score-adjusted analysis among vasopressor-treated patients (OR 3.0, 95 % CI 1.3, 7.2, p = 0.013); this was further confirmed by propensity-score-matched analysis. Adrenaline was also associated, independent of prior cardiac arrest, with marked worsening of cardiac and renal biomarkers during the first days. Dobutamine and levosimendan were the most commonly used inotropes (49 % and 24 %). There were no differences in mortality, whether noradrenaline was combined with dobutamine or levosimendan. CONCLUSION: Among vasopressors and inotropes, adrenaline was independently associated with 90-day mortality in CS. Moreover, adrenaline use was associated with marked worsening in cardiac and renal biomarkers. The combined use of noradrenaline with either dobutamine or levosimendan appeared prognostically similar.
Keywords: senioři; Survival; Propensity score; Inotropes; přežití tkáně; vazokonstriktory; Middle Aged; Vasopressors; mužské pohlaví; Adult; Tissue Survival; mortalita v nemocnicích; Cardiogenic shock; Shock, Cardiogenic; ženské pohlaví; adrenalin; Humans; kardiotonika; Hemodynamics; Mortality; hemodynamika; Propensity Score; Adrenaline; Cardiotonic Agents; lidé středního věku; Hospital Mortality; tendenční skóre; kardiogenní šok; Vasoconstrictor Agents; dospělí; Female; Aged; Epinephrine; Vasoactive medication; lidé; Male